Postactivation potentiation and change of direction speed in elite academy rugby players - Marshall, J.; Turner, A. N.; Jarvis, P. T.; Maloney, S. J.; Cree, J. A.; Bishop, C. J. (The Journal of Strength and Conditioning Research, 2019)
This study investigated the effect of preceding proagility sprints with maximal isometric squats to determine if postactivation potentiation (PAP) could be harnessed in change of direction speed. Sixteen elite under-17 rugby union players (age: 16 ± 0.41 years; body mass: 88.7 ± 12.1 kg; height: 1.83 ± 0.07 m) from an Aviva Premiership rugby club were tested. Subjects performed a change of direction specific warm-up, followed by 2 baseline proagility tests. After 10-minute recovery, 3 × 3-second maximal isometric squats with a 2-minute recovery between sets were completed as a conditioning activity (CA) on a force plate where peak force and mean rate of force development over 300 milliseconds were measured. The proagility test was repeated at set time intervals of 1, 3, 5, and 7 minutes after the CA. Overall proagility times were significantly slower (p < 0.05) at 1 minute post-CA compared with the baseline (3.3%), with no significant differences occurring at 3, 5, or 7 minutes post-CA. Therefore, it appears that performing multiple sets of maximal isometric squats do not enhance proagility performance.